RETRACTED: Potamogeton perfoliatus L. Extract Attenuates Neuroinflammation and Neuropathic Pain in Sciatic Nerve Chronic Constriction Injury-Induced Peripheral Neuropathy in Rats - Mahmoud, Mona F.; Rezq, Samar; Alsemeh, Amira E.; Abdelfattah, Mohamed A. O.; El-Shazly, Assem M.; Daoud, Rachid; El Raey, Mohamed A.; Sobeh, Mansour (Frontiers in Pharmacology, 2021)
Sciatic nerve injury is often associated with neuropathic pain and neuroinflammation in the central and peripheral nervous systems. In our previous work, Potamogeton perfoliatus L. displayed anti-inflammatory, antipyretic and analgesic properties, predominantly via the inhibition of COX-2 enzyme and attenuation of oxidative stress. Herein, we extended our investigations to study the effects of the plant’s extract on pain-related behaviors, oxidative stress, apoptosis markers, GFAP, CD68 and neuro-inflammation in sciatic nerve chronic constriction injury (CCI) rat model. The levels of the pro-inflammatory marker proteins in sciatic nerve and brainstem were measured with ELISA 14 days after CCI induction. Pretreatment with the extract significantly attenuated mechanical and cold allodynia and heat hyperalgesia with better potential than the reference drug, pregabalin. In addition, CCI lead to the overexpression of prostaglandin E2 (PGE2), inducible nitric oxide synthase (iNOS), tumor necrosis alpha (TNFα), nuclear factor κB (NF-κB), cyclooxygenase-2 (COX-2), 5-lipoxygenase (5-LOX), and NADPH oxidase-1 (NOX-1) and decreased the catalase level in sciatic nerve and brainstem. The observed neuro-inflammatory changes were accompanied with glial cells activation (increased GFAP and CD68 positive cells), apoptosis (increased Bax) and structural changes in both brainstem and sciatic nerve. The studied extract attenuated the CCI-induced neuro-inflammatory changes, oxidative stress, and apoptosis while it induced the expression of Bcl-2 and catalase in a dose dependent manner. It also decreased the brainstem expression of CD68 and GFAP indicating a possible neuroprotection effect. Taking together, P. perfoliatus may be considered as a novel therapy for neuropathic pain patients after performing the required clinical trials.